ANALISIS EFISIENSI BIAYA BAHAN BAKU MENGGUNAKAN METODE JUST IN TIME (JIT) STUDI KASUS CV. SOYA AULA DI ACEH BESAR - Nabila, Nabila; Jalaluddin, Jalaluddin (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2021)
This study aims to analyze the application of the Just In Time method to improve the cost efficiency of raw materials at CV. Soya Aula. This study used descriptive qualitative method. The data used are primary data and secondary data. Primary data using observation, interview, and documentation techniques. The data analysis used the cost of raw materials where the application of Just In Time analysis performs the calculations with the MRP and MCE methods. The results of this study indicate that there is a decrease in the cost of raw materials after the application of the Just In Time method. By using the MRP method for purchasing raw materials per day, the cost of raw materials has decreased by 12.24%. And by using the MCE method to measure the level of efficiency, it is known that the efficiency per day is 95.6%, by choosing non value added and value added activities.